'It is Medicine': Narratives of Healing from the Aotearoa Digital Storytelling as Indigenous Media Project (ADSIMP). (September 2014) - Beltrán, Ramona; Begun, Stephanie
Recently, narrative has emerged as an important concept in interrupting the transmission of intergenerational trauma in Indigenous communities. For many Indigenous peoples, narrative in the form of storytelling is a fundamental traditional cultural practice. This article presents findings from a community-based digital storytelling (DS) workshop that focused on eliciting stories of resiliency amidst historical trauma (HT) in the Māori community. The principal investigator worked with Māori community members to create digital stories focused on cultural strengths. Post-workshop in-depth interviews were then conducted to explore participant experiences in the workshop. Analyses of narratives reveal the importance of language to name and define HT, describe the transformative nature of the DS workshop and reaffirm the great promise that DS demonstrates as a healing tool in the disruption of HT in future work with Indigenous communities.